2003
DOI: 10.1046/j.1469-0691.2003.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Source of infection and other factors associated with case fatality in community-acquired bacteremia—a Danish population-based cohort study from 1992 to 1997

Abstract: As an undetermined source of infection was strongly associated with CFR, physicians should be aware of the significance of identifying and eliminating a source of infection, and more efforts should be directed at timely and appropriate empirical antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
4
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 40 publications
7
80
4
2
Order By: Relevance
“…This result is also similar to another study. 12 Moreover, Pedersen et al 20 reported a 30-day mortality rate of 13% to 15% in patients with primary bacteremia. The incidence (13.2%) and the mortality rate (15.9%) of primary bacteremia in our study were close to those of this previous report.…”
Section: Discussionmentioning
confidence: 99%
“…This result is also similar to another study. 12 Moreover, Pedersen et al 20 reported a 30-day mortality rate of 13% to 15% in patients with primary bacteremia. The incidence (13.2%) and the mortality rate (15.9%) of primary bacteremia in our study were close to those of this previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical antibiotic therapy was considered appropriate when an antibiotic, that had in vitro activity against the causative organism, was given during the first 48 h. If the isolates were resistant or if the dose or the route of administration was insufficient, treatment was considered to be inappropriate (Pedersen et al, 2003;Schonheyder and Sogaard, 2010;Lim et al, 2014).…”
Section: Variables and Definitionsmentioning
confidence: 99%
“…Bacteremia is a serious condition with an overall in-hospital mortality above 20% (15,19). Early administration of appropriate empirical antibiotic treatment has repeatedly been associated with improved survival in patients with bacteremia (5,15,27), yet up to 40% of all patients with bacteremia receive inadequate antibiotic treatment until the first notification of a positive blood culture (5,6,22,24).…”
mentioning
confidence: 99%
“…At this time, 12 to 20% of the patients may not have started antibiotic treatment, and in another 30 to 45% of patients, the Gram stain result is followed by a change in the empirical treatment (2,7,19,22,24). The Gram stain report has been shown to have a much greater impact on antimicrobial treatment than provision of cultural identification and antimicrobial susceptibility test results (17,22), and recently Hautala et al (12) reported that combining Gram stain results with information on whether the infection was hospital or community acquired could further improve the appropriateness of the antibiotic treatment.…”
mentioning
confidence: 99%